2009
DOI: 10.1386/ijcm.2.2-3.183_1
|View full text |Cite
|
Sign up to set email alerts
|

The Gettin' Higher Choir: Exploring culture, teaching and learning in a community chorus

Abstract: The purpose of the study was to examine musical teaching and learning in an informal context in order to glean information and strategies that may be helpful to teachers and students in more formal settings. Through an ethnographic approach, the researcher examined the particular culture of the Gettin' Higher Choir (GHC) to gain a deep understanding of the GHC experience and examine the teaching and learning processes of this 300+-member organization. Data collection techniques consisted of observation, interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…Characterised as a fraternity, the Accafellows described their connection to one another as that of a family and that they could rely on current members as well as former members to support in a variety of ways. As shown in earlier music education research (e.g., Adderley, Kennedy, and Berz 2003;Hylton 1981;Kennedy 2009;Kwan 2002;Sweet 2010), a common extramusical benefit of musical ensemble participation is that of social connections. Music educators might explore providing opportunities to enhance personal connections among members.…”
Section: Music Education Research 33mentioning
confidence: 86%
See 3 more Smart Citations
“…Characterised as a fraternity, the Accafellows described their connection to one another as that of a family and that they could rely on current members as well as former members to support in a variety of ways. As shown in earlier music education research (e.g., Adderley, Kennedy, and Berz 2003;Hylton 1981;Kennedy 2009;Kwan 2002;Sweet 2010), a common extramusical benefit of musical ensemble participation is that of social connections. Music educators might explore providing opportunities to enhance personal connections among members.…”
Section: Music Education Research 33mentioning
confidence: 86%
“…In fact, a number of studies have investigated music making among professional pop musicians, community choruses, teen garage bands and hip-hop artists (Bell 2000;Campbell 1995;Finnegan 1989;Fornas, Lindberg, and Sernhede 1995;Green 2001;Jaffurs 2004;Kennedy 2003Kennedy , 2009Sö derman and Folkestad 2004;Townsend 1997). One of the purposes of such research is to help music educators understand how music making takes place in these informal settings and gain knowledge that may be used in formal music education settings.…”
Section: Music Making In Informal Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following examples list work published by those who would probably describe themselves as having community music interests, at least as evidenced by the context of publication, followed by those who would seem to be more obviously ethnomusicological in orientation: Stephen J. Messenger's (2013) work on sharing practices and community building among online jamband aficionados has something in common with René Lysloff's (2003) study of music composition through the use of mods (software); the strategies for preserving and promoting community folk music traditions considered by Karlsen, Westerlund, Partti and Solbu (2013) in relation to Scandinavia, or Shiobara (2011) with respect to the nagauta tradition of Japan, do not look out of place alongside the studies of east Asian cultural heritage found in Keith Howard's (2012) edited volume on Music as Intangible Cultural Heritage; and the quintessentially participatory activity of choral singing finds its way into a number of studies in both domains, such as Mary Copeland Kennedy's (2009) study of the Gettin' Higher Choir or Caroline Bithell's (2014) research into the natural voice movement; and so forth. Indeed, some recent publications in the International Journal of Community Music are quite explicit in their adoption of ethnomusicological heritage and methodologies (e.g., Balandina, 2010;Jones, 2014).…”
mentioning
confidence: 99%